Code - Tyler Sheldon (Symphony in the Flint Hills, 2016)
In the Flint Hills when walking, touch the bluestem half way down the blade to feel a finished thought not yet in words.
Keywords: Flint Hills; bluestem; squirrels; cottonwoods; redemption; poetry; Fading Places; Jody Lightner